Decomposing the meridional heat transport in the climate system - Yang, Haijun; Li, Qing; Wang, Kun; Sun, Yu; Sun, Daoxun (Climate Dynamics, 2015)
The meridional heat transport (MHT) in the climate system is investigated using a state-of-the-art coupled climate model (CESM1.0). This work decomposes the MHT and studies their physics in detail. The meridional ocean heat transport (OHT) can be decomposed into the contributions from the Euler mean circulation, bolus circulation, sub-mesoscale circulation and dissipation. The Euler mean heat transport dominates the total OHT in most latitudes, except that in the Southern Ocean (40-50 degrees S) where the OHT is determined by the eddy-induced circulation and dissipation. In the Indo-Pacific the OHT is fulfilled by the wind-driven circulation, which dominates the total global OHT in the tropics. In the Atlantic the OHT is carried by both the wind-driven circulation and the thermohaline circulation, and the latter dominates the total OHT in the midhigh latitudes. The meridional atmosphere heat transport consists of the dry static energy (DSE) and latent energy (LE) transport. In the tropics the LE transport is equatorward and compensates partially the poleward DSE transport. In the extratropics, the LE and DSE are poleward and reinforce one another, both of which are dominated by the eddy components. The LE transport can be considered as the "joint air-sea mode" since the ocean controls the moisture supply. It can be also precisely obtained from the evaporation minus precipitation over the ocean and thus this work quantifies the individual ocean basin contributions to the LE transport. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000351459800024&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Meteorology & Atmospheric Sciences SCI(E) 5 ARTICLE hjyang@pku.edu.cn 9-10 2751-2768 44